2022
DOI: 10.1183/23120541.00584-2021
|View full text |Cite
|
Sign up to set email alerts
|

Trends in non-receipt of recommended COPD medication

Abstract: This manuscript has recently been accepted for publication in the ERJ Open Research. It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJOR online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…found that only 12% received guideline-discordant inhaler regimens (defined as not receiving LAMA or ICS + LABA) among patients hospitalized for COPD exacerbation or patients with ≥2 COPD exacerbations in Ontario, Canada. 12 , 42 Among COPD patients discharged from hospitals in Italy, Di Martino et al. reported that 35% received guideline-discordant inhaler prescriptions, defined as not receiving LAMA or LABA.…”
Section: Discussionmentioning
confidence: 99%
“…found that only 12% received guideline-discordant inhaler regimens (defined as not receiving LAMA or ICS + LABA) among patients hospitalized for COPD exacerbation or patients with ≥2 COPD exacerbations in Ontario, Canada. 12 , 42 Among COPD patients discharged from hospitals in Italy, Di Martino et al. reported that 35% received guideline-discordant inhaler prescriptions, defined as not receiving LAMA or LABA.…”
Section: Discussionmentioning
confidence: 99%